PENGARUH DISIPLIN KERJA, MOTIVASI, DAN GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP KINERJA KARYAWAN PT. ANANDA PUTRA NANOTECH INDONESIA SUKOHARJO JAWA TENGAH - Mahdi, Irham; Suci Utami Wikaningtyas (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the effects of work discipline, work motivation, and democratic leadership style on employee performance at PT Ananda Putra Nanotech Indonesia in Sukoharjo, Central Java. Employee performance is a crucial determinant of organizational success in global competition, requiring disciplined, motivated, and effectively managed human resources. This research employs a quantitative approach using a causal associative design. The population consists of permanent employees with a minimum tenure of one year, and sixty respondents were selected through purposive sampling. Data were collected via online questionnaires using a six point Likert scale and analyzed with multiple linear regression supported by IBM SPSS Statistics version twenty five. The findings show that work discipline has a positive and significant partial effect on employee performance, indicating that rule compliance and punctuality improve effectiveness. Democratic leadership style also significantly enhances performance by encouraging participation, communication, and involvement. However, work motivation shows no significant partial effect. Simultaneously, all variables significantly influence employee performance, with 48.4 percent of performance variation explained, while remaining variance is affected by other external factors. This result highlights the importance of managerial discipline systems and participative leadership practices for sustaining organizational productivity and long term performance improvement across operational contexts.